Building fabric improvement and heat pump deployment: a set of policy conundrums - Killip, G; Topouzi, M; Fawcett, T (European Council for an Energy Efficient Economy, 2024)
Minimum building energy efficiency standards and retrofit targets for fabric improvement have long been a cornerstone of effective policy for energy demand. However, there is increasing policy focus on residential heating (and cooling) being provided from renewable electricity via heat pumps. Do fabric standards matter anymore and, if so, why? This paper looks at the trade-offs and policy complexity facing countries which are currently largely dependent on fossil fuel boilers for heating. What should the balance be between mandating building fabric improvement and heat pump deployment, what are the choice criteria, and who gets a say? The paper examines building interventions through the concept of 'trigger points.' It evaluates a segmented market approach and proposes a policy framework that emphasises 'understanding first' as a strategy to facilitate informed decision-making, rather than imposing specific measures. For example, the mandate to replace all fossil-fired heating systems presents a new opportunity for policy intervention: transitioning to a new heating system can act as a trigger for at least minimal fabric improvements. The paper explores various tests associated with the 'understanding first' approach, discussing how to strike a balance between simplicity and complexity in policy. It also delves into practical considerations for implementing the 'understanding first' approach, including affordability, energy security, and fostering a just energy transition. Understanding is identified as a necessary, but not sufficient, aspect of policy for the decarbonisation of heating. The paper concludes that while a deeper understanding is crucial, it must also translate into new narratives for different actors to enable tangible, measurable changes in the built environment. There is no one right answer – and policy needs the flexibility to recognise this. Setting minimum quality standards for deployment, and a policy framework which allows for local decision-making within nationally (and internationally) determined targets is likely to be part of the answer. This paper sets out the challenge for policy in devolution and coordination, providing a set of unresolved conundrums that future policy needs to meet. The discussion presented aims to enrich and provoke further debate, rather than offering conclusive solutions to complex problems.